2007
DOI: 10.1002/art.22851
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the development of knee pain with enlarging bone marrow lesions on magnetic resonance imaging

Abstract: Objective. Results of cross-sectional studies have suggested that bone marrow lesions (BMLs) visualized on magnetic resonance imaging (MRI) are related to knee pain, but no longitudinal studies have been done. This study was undertaken to determine whether enlarging BMLs are associated with new knee pain.Methods. Subjects ages 50-79 years with knee osteoarthritis (OA) or at high risk of knee OA were asked twice at baseline about the presence of knee pain, aching, or stiffness (classified as frequent knee pain)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
334
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 403 publications
(351 citation statements)
references
References 21 publications
12
334
2
3
Order By: Relevance
“…The present results and those from previous knee MRI studies (28)(29)(30) highlight the importance of evaluating risk factors predictive of cartilage volume loss in knee OA. For instance, it is known that the presence of meniscal lesions or BML is predictive of disease progression (5,11,26,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 76%
“…The present results and those from previous knee MRI studies (28)(29)(30) highlight the importance of evaluating risk factors predictive of cartilage volume loss in knee OA. For instance, it is known that the presence of meniscal lesions or BML is predictive of disease progression (5,11,26,(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 76%
“…Felson et al 18,19 were the first authors to show a correlation between BME and symptomatic OA because patients with painful knee OA were 2.5 times more likely to have BME on MRI. Although there is no current literature relating to treatment of OCD lesions by use of this technique, Sharkey et al 20 recently reported its use in the treatment of BME associated with OA in a 51-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports were extremely enthusiastic about the role of BMLs in knee OA. They suggested that BMLs were associated with knee pain [15], could be predictive of progression [16] especially if they enlarged [17] or were associated with varus or valgus angulation [16]. Later reports, however, were less clear-cut even suggesting that BMLs were not only unassociated with Western Ontario and McMaster Universities index of OA scores (WOMAC™) [18,19] and other measures of patient symptoms but also fluctuated over a period of time, resolving and/or worsening with new lesions coming and going elsewhere in the same joint [20,21].…”
Section: So Where Does the Problem Lie?mentioning
confidence: 99%